2018
DOI: 10.1002/lary.27574
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Balloon Diameter on Dilation Outcomes in a Model of Rabbit Subglottic Stenosis

Abstract: Objective To determine the appropriate balloon size for dilation using a previously described reproducible survival animal model of subglottic stenosis. Study Design Prospective animal study. Methods We conducted a prospective study including 16 New Zealand White rabbits. The airway of each animal was sized with an endotracheal tube (ETT), and subglottic stenosis (SGS) was endoscopically induced using Bugbee electrocautery to 75% of the circumference of the subglottis, followed by 4‐hour intubation. Two weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Schweiger et al reported that balloon dilation procedure treated SGS in all rabbits, which underwent the treatment with an 8 mm diameter balloon, whereas it increased the airway diameter when a 6 mm diameter balloon was used, but it did not treat the SGS completely. 30 Lisy et al demonstrated that balloon dilation procedure avoided the need for tracheostomy in 80% of cases following balloon dilation. 36 However, in some cases balloon dilation had to be performed multiple times to treat SGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schweiger et al reported that balloon dilation procedure treated SGS in all rabbits, which underwent the treatment with an 8 mm diameter balloon, whereas it increased the airway diameter when a 6 mm diameter balloon was used, but it did not treat the SGS completely. 30 Lisy et al demonstrated that balloon dilation procedure avoided the need for tracheostomy in 80% of cases following balloon dilation. 36 However, in some cases balloon dilation had to be performed multiple times to treat SGS.…”
Section: Discussionmentioning
confidence: 99%
“…Subglottic stenosis was induced by cauterization of 75% of the posterior subglottic region followed by 4‐hour intubation carried out using a 3.5 mm ETT as shown in Figure 1B,C 30 . Intubation of the rabbits after cauterization was performed to exacerbate the development of stenoses.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these data suggest that a longer duration of balloon dilation combined with topical ciprofloxacin-dexamethasone produces an improved clinical result as compared with a short duration of balloon dilation by decreasing restenosis severity without increasing perioperative complications. While there are no published guidelines for the ideal duration of subglottic balloon dilation, several studies cite a 30-second dilation 12,18 or to maintain balloon inflation until desaturation. 2,3 In this study, long-duration balloon dilation was defined as 30 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no published guidelines for the ideal duration of subglottic balloon dilation, several studies cite a 30‐second dilation 12 , 18 or to maintain balloon inflation until desaturation 2 , 3 . In this study, long‐duration balloon dilation was defined as 30 seconds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation